The relationship between cancer detection in mammography and image quality measurements. Issue 4 (April 2016) - Mackenzie, Alistair; Warren, Lucy M.; Wallis, Matthew G.; Given-Wilson, Rosalind M.; Cooke, Julie; Dance, David R.; Chakraborty, Dev P.; Halling-Brown, Mark D.; Looney, Padraig T.; Young, Kenneth C.
Highlights: Calcification cluster detection is related to image quality measured by CDMAM phantom. CDMAM tests discriminate between clinically acceptable and unacceptable systems. Image quality standards in European Guidelines need reviewing. Abstract: Purpose: To investigate the relationship between image quality measurements and the clinical performance of digital mammographic systems. Methods: Mammograms containing subtle malignant non-calcification lesions and simulated malignant calcification clusters were adapted to appear as if acquired by four types of detector. Observers searched for suspicious lesions and gave these a malignancy score. Analysis was undertaken using jackknife alternative free-response receiver operating characteristics weighted figure of merit (FoM). Images of a CDMAM contrast-detail phantom were adapted to appear as if acquired using the same four detectors as the clinical images. The resultant threshold gold thicknesses were compared to the FoMs using a linear regression model and an F -test was used to find if the gradient of the relationship was significantly non-zero. Results: The detectors with the best image quality measurement also had the highest FoM values. The gradient of the inverse relationship between FoMs and threshold gold thickness for the 0.25 mm diameter disk was significantly different from zero for calcification clusters ( p  = 0.027), but not for non-calcification lesions ( p  = 0.11). Systems performing just above the minimum image quality level set in the European Guidelines for Quality Assurance in Breast Cancer Screening and Diagnosis resulted in reduced cancer detection rates compared to systems performing at the achievable level. Conclusions: The clinical effectiveness of mammography for the task of detecting calcification clusters was found to be linked to image quality assessment using the CDMAM phantom. The European Guidelines should be reviewed as the current minimum image quality standards may be too low.